Guarantee of equality in politics? The media discourse analysis on the subject of introducing the gender parity into electoral law in Poland - Strzemecka, Stella (Wydawnictwo Naukowe UAM, 2014)
The project is aiming at the quality analysis of a media discussion about introducing the gender parity to electoral law and the analysis of the activities of the Association of Congress of Women. Selected press publications are the basis of the quality analysis (according to the Critical Discourse Analysis) taken from the most opinion‐creating journals. The objective of this paper is to identify the discourse (civil; non‐civil) of analyzed journals.
Keywords: gender parity; electoral lists; quota solution; Poland; rhetoric of the equality; CDA